DESKRIPSI PEMAHAMAN MAHASISWA ILMU KEOLAHRAGAAN MENGENAI KONSEP OVERUSE SYNDROME PADA OLAHRAGA ENDURANCE - Arif Wellmen Tumanggor; Grasius Steven Sihotang; Muhammad Fadil; Ahmad Sopiyan; Mawardinur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Overuse syndrome is one of the most common health problems encountered in sports activities, particularly in endurance sports that require repetitive physical activity over prolonged durations and at specific intensities. This condition results from the accumulation of mechanical stress on body tissues that occurs continuously without adequate recovery. Injuries caused by overuse syndrome can negatively affect athletic performance, disrupt training processes, and increase the risk of long-term musculoskeletal disorders. In the context of sports education, students of Sport Science need to possess a comprehensive understanding of the concept of overuse syndrome, as they are being prepared to become professionals involved in sports coaching, physical education, athletic training, and community fitness development. This article aims to describe Sport Science students’ understanding of the concept of overuse syndrome in endurance sports based on a review of recent scientific literature. The study employed a library research method by analyzing various scientific articles and reference books related to the topic. The findings indicate that most students understand overuse syndrome as an injury resulting from excessive training and repetitive movements. Their understanding includes the causes, symptoms, impacts on sports performance, and preventive measures that can be implemented. However, numerous studies suggest that students’ knowledge regarding physiological mechanisms, biomechanical factors, early injury detection, and recovery management still requires further enhancement through more in-depth learning. Furthermore, advances in sport medicine and sports rehabilitation require students to develop a more comprehensive understanding of the relationships among training load, fatigue, physiological adaptation, and injury risk. Therefore, integrating injury prevention, exercise physiology, biomechanics, and sports medicine into the Sport Science curriculum is essential to equip students with the competencies needed to identify, prevent, and manage overuse syndrome in endurance sports professionally. Keywords: overuse syndrome, endurance sports, Sport Science students, sports injuries, sport medicine.